Penegakan Hukum Pidana Terhadap Tindak Pidana Pencucian Uang Gayus Tambunan di Indonesia - Fardana, Andhika Yudha; Widijowati, Dijan; Hakim, Lukman (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
The financial system and the national economy are significantly affected by complex money laundering crimes (ML), with criminal law policies regulated in several laws, including Law No. 8 of 2010, being used in Indonesia to combat money laundering. The main objective of this study is to examine the effectiveness of criminal law policies in preventing money laundering, the challenges faced by law enforcement agencies, and the Gayus Tambunan case – a striking illustration of the weakness in the application of law in Indonesia. This study uses a statutory approach, literature review, and normative legal methodology. The findings of this study show that although there is a legal framework in place, there are still several barriers in implementation and law enforcement, including poor coordination between agencies, insufficient human resources, and low public awareness and involvement. Therefore, to build an efficient and just law enforcement system in combating money laundering in Indonesia, it is crucial to strengthen regulations, enhance the capabilities of law enforcement agencies, and educate the public.